2008
DOI: 10.1103/physrevlett.101.215502
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Mechanical Strain to Mitigate the Intrinsic Loss Mechanisms in Oscillating Metal Nanowires

Abstract: We utilize classical molecular dynamics to study energy dissipation (the Q factors) of doubly clamped copper nanowire nanoresonators undergoing flexural oscillations. We find that the application of tensile strain effectively mitigates both the intrinsic surface and thermal losses, with improvements in Q by a factor of 3-10 across a range of operating temperatures. We also find that the nanowire Q factors are not dependent on the surface area to volume ratio, but instead their aspect ratio, and that the Q fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…Different variants of method A have been used earlier [35][36][37] in the computation of Q factor. In this method, we perturb the desired mode of the structure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different variants of method A have been used earlier [35][36][37] in the computation of Q factor. In this method, we perturb the desired mode of the structure.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that tensile stress can be used to enhance the Q factor for a nano-wire. 36,45 It would, therefore, be useful to study the role of tension for the case of intrinsic damping. We develop scaling relations for the variation of Q factor with the initial tension using continuum theory.…”
Section: B Role Of Tensionmentioning
confidence: 99%
“…Different methods have been used in the literature to calculate the Q-factor. 138,144,[149][150][151] The maximum potential energy (E) is reduced to E À DE at the end of each oscillation cycle due to energy loss or damping, where DE represents the energy loss in each oscillation cycle. The Q-factor is thus defined as Q ¼ 2pE=DE.…”
mentioning
confidence: 99%
“…Thus, the change of the external energy over time will be tracked for the calculation of Q . The external energy is defined as the difference of the potential energy before and after the initial excitation is applied to the testing sample [32]. Regarding the resonance frequency, a discrete Fourier transform will be applied [33].…”
Section: Resultsmentioning
confidence: 99%